Implementation of Digital Business Regulations in The Corporate Governance of PT Arina Shiva Group: an Empirical Legal Analysis of Legal Compliance as The Basis for Regulatory Harmonization in The Era of Globalization - Achmad Shiva’ul Haq Asjach; Hidayatullah Hidayatullah; Herbin Marulak Siahaan (Edunity Kajian Ilmu Sosial dan Pendidikan, 2026)
This research aimed to analyze the implementation of digital business regulations within the governance framework of PT Arina Shiva Group, examine the company’s level of legal compliance with applicable laws and regulations, and formulate a regulatory harmonization model to strengthen digital business governance in the era of globalization. The research employed an empirical juridical method using statutory, conceptual, case, and comparative approaches. Data were obtained through literature reviews, analysis of corporate documents, observations of digital business governance practices, and interviews with authorized representatives of PT Arina Shiva Group. Furthermore, the data were analyzed qualitatively through the processes of data reduction, data presentation, and conclusion drawing by comparing legal norms (das sollen) with their implementation in practice (das sein). The findings indicate that the implementation of digital business regulations at PT Arina Shiva Group has generally accommodated various national legal provisions related to business entity legality, electronic transactions, corporate governance, and intellectual property rights protection. However, the study also identified the need to strengthen legal compliance mechanisms that are more adaptive to the dynamics of global digital regulations, particularly in the areas of personal data protection, artificial intelligence governance, cybersecurity, and the application of good digital governance principles. This study proposed a digital business regulatory harmonization model based on corporate legal compliance that integrates national regulatory frameworks with digital governance practices.